Historical Titles of the Roman Pope and his Universal Jurisdiction in Episcopal Appointments (Stato, Chiese e pluralismo confessionale, 2025)
If papal authority over the Latin Church can be linked to the ultra-metropolitan jurisdiction of the Bishop of Rome as Patriarch of the West in the first millennium, as well as to his primacy over the Italian Church during the same period, the pontifical solicitude towards the Eastern Catholic Churches realises the exercise of the full ordinary and immediate power of the Roman Pontiff, a solicitude that takes concrete form in a variety of ways to protect and safeguard their traditions and ecclesial specificities.
Keywords: Eastern Churches; Patriarchate of the West; Roman Pontiff